SISTEM OTOMATISASI AEROPONIK INDOOR PADA TANAMAN SAWI BERBASIS INTERNET OF THINGS - Hannan, Abdul; Rismawan, Tedy; Sari, Kartika (Universitas Teknokrat Indonesia, 2025)
Abstract The increasing global population growth poses serious challenges in meeting the world's food needs, and one promising solution is to increase productivity and efficiency in agriculture through Internet of Things (IoT) technology. In order to achieve this, this study aims to develop and implement an Internet of Things (IoT)-based automation system for indoor aeroponic farming, specifically designed to cultivate mustard flowers, utilizing advanced LED Grow Light technology for optimal growth conditions, a capacitive soil moisture sensor to detect uneven condensation of nutrients, and a pH sensor to maintain the balance of nutrient solution. The NodeMCU ESP32 microcontroller, alongside the Arduino platform, serves as the central control unit of the system, autonomously monitoring and regulating the growth environment. The findings demonstrate how effectively this technology can detect and adjust plant growth parameters, such as air temperature (99.24%), water temperature (98.63%), nutrient content (96.50%), water height (94.20%), and water pH (98.88%). In addition, the system successfully provides lighting using an L.E.D. Grow Light that is on for 12 hours every day, and effectively detects condensation unevenness, which then provides notifications via Telegram. The increased efficiency achieved by this system shows great potential in supporting efforts to fulfil global food needs through IoT technology. Keywords: Aeroponics, IoT, LED Grow Light, pH Sensor, Agriculture Automation. Abstrak Pertumbuhan populasi global yang terus meningkat menimbulkan tantangan serius dalam memenuhi kebutuhan pangan dunia, dan salah satu solusi yang menjanjikan adalah dengan meningkatkan produktivitas serta efisiensi dalam pertanian melalui teknologi Internet of Things (IoT). Untuk mencapai hal ini, penelitian difokuskan pada pengembangan dan penerapan sistem aeroponik dalam ruangan berbasis IoT yang bertujuan untuk meningkatkan budidaya tanaman sawi, dengan memanfaatkan LED Grow Light untuk pencahayaan optimal, capacitive soil moisture sensor untuk mendeteksi ketidakmerataan pengembunan nutrisi, serta sensor pH untuk menjaga keseimbangan larutan nutrisi. Sistem ini menggunakan mikrokontroler NodeMCU ESP32 dan Arduino sebagai pusat kendali untuk memantau dan mengontrol lingkungan tumbuh secara otomatis. Hasil penelitian menunjukkan bahwa sistem ini mampu memantau dan mengendalikan kondisi tanaman dengan akurasi tinggi, seperti suhu udara (99,24%), suhu air (98,63%), kandungan nutrisi (96,50%), tinggi air (94,20%), dan pH air (98,88%). Selain itu, sistem ini berhasil memberikan pencahayaan menggunakan LED Grow Light yang menyala selama 12 jam setiap hari, serta mendeteksi ketidakmerataan pengembunan dengan efektif, yang kemudian memberikan notifikasi melalui Telegram. Peningkatan efisiensi yang dicapai oleh sistem ini menunjukkan potensi besar dalam mendukung upaya pemenuhan kebutuhan pangan global melalui teknologi IoT. Kata Kunci: Aeroponik, IoT, LED Grow Light, Sensor pH, Otomatisasi Pertanian.